Comparison of student’s learning outcomes using mind map with Concet Mapping in Cooperative Learning Type Of Think Pair Share (TPS) For Animalia Material - wita ferwati (Jurnal Scientia, 2022)
This research was conducted to find solutions in biology learning which tend to have quite dense and rotematerial and contain Latin that students must understand, one of which is the Animalia subject in class X.So that students can be actively involved and help students take notes. to make it easier to rememberinformation. So the solution offered is to use a Think Pair Share (TPS) cooperative learning model usinga Mind Map (mind map) and Concept Mapping (concept map). The purpose of this study was todetermine the difference in student learning outcomes using Mind Map with students using ConceptMapping in Think Pair Share (TPS) cooperative learning with Animalia material at SMA Negeri 1 RantauUtara.This research includes experimental research. The population in this study were students of class XSMA N 1 Rantau Utara, who were enrolled in the 2021/2022 school year. The sample in this study wasclass X3 as the experimental class I with 37 students and class X5 as the experimental class II with 36students. The data analysis technique was using the t-test, based on the results of the final test dataanalysis, the results of this study were the average learning outcomes of Biology Experiment Class Iwhich were treated in the form of implementing a Think Pair Share (TPS) cooperative learning modelusing a Mind map (mind map). good compared to the Experiment II class which was treated in the formof applying the TPS type cooperative learning model using Concept Mapping (Concept Map).